HUBUNGAN LAMA MENYUSUI PADA MULTIPARA DENGAN KEJADIAN KANKER PAYUDARA DI RSUD DOKTER SOEDARSO PONTIANAK - ., Edina Theodora Agustina Sagala (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Breast cancer is the most common malignancy among women patient in RSUD Dokter Soedarso Pontianak. One of thereproductive factors that associated with decrease risk of breast cancer isbreastfeeding. Breastfeeding is reported lower in multiparous women.Objective: This research aimed to evaluate the association betweenduration of breastfeeding in multiparous women with breast cancerincidence at RSUD Dokter Soedarso Pontianak. Method: This researchwas hospital based case control study that has been conducted atoncology surgery clinic at RSUD Dokter Soedarso Pontianak from August2013 to August 2014, samples were 24 women with breast cancer and 24controls. Research instruments were medical record and questionnaire.Result: There is no significant association between breastfeeding durationin multiparous women and breast cancer incidence (p = 0.43).Breastfeeding characteristics that associated with decrease risk of breastcancer are age at first lactation 25-29 years (OR=0.50), number of childrenbreastfed â‰¥4 children (OR=0.47), age at last lactation â‰¥40 years(OR=0.25), average breastfeeding duration >12 months (OR=0.19), andlifetime breastfeeding duration >24 months (OR=0.46). Risk factors thatassociated with breast cancer incidence are family history of breastcancer, menopause, and use of ERT, cigarette, and alcohol (p<0.05).Conclusion: Breastfeeding duration in multiparous women is notassociated with breast cancer incidence at RSUD Dokter SoedarsoPontianak. Â Key words: Breast cancer, breastfeeding duration, multiparous women,risk factor 1) Medical School, Faculty of Medicine, University of Tanjungpura, Pontianak, West Borneo 2) Department of General Surgery, RSUD Dokter Soedarso, Pontianak, West Borneo 3) Department of Pediatric, Faculty of Medicine, University of Tanjungpura Pontianak, West Borneo